Health services and immigration in Andalusia (Spain): a view from inside - Belmonte García, Teresa; Checa Olmos, Juan Carlos; Arjona Garrido, Ángeles (Saúde e Sociedade, 2012)
The aim of this paper is to understand the view of both users and professionals on certain aspects of the management of the Spanish National Health System, especially with regard to dealing with diversity. In order to do so, the model of access to health care is analyzed, as well as the resources employed in health care and the sanitary demand made by immigrants in Andalusia (Spain).The data were collected through the performance of 15 semi-structured interviews with immigrants and 7 with professionals from the Andalusian health system. In addition, the field work is complemented by direct observation of the use of the public health services for one year. The results show, first, that although immigrants have universal access to health care, they must overcome a series of administrative, linguistic and cultural barriers, which prevent a totally satisfactory use. These limits are avoided, in most cases, through social networks. Second, the resources used have not been adapted to the specific needs of the immigrant population, such as the accumulation of good health, subjective assessment of good health and the aggressions or damage suffered by good health. And third, the use made by immigrants of the health system does not differ from that performed by the locals regarding both frequency and pathologies.